Microbes, molecular mimicry and molecules of mood and motivation. (February 2016) - Morris, J.A.; Broughton, S.J.; Wessels, Q.
Abstract: The hypothesis proposed is that functional disorders, such as irritable bowel syndrome, chronic fatigue syndrome and anorexia nervosa are caused by auto-antibodies to neuronal proteins induced by molecular mimicry with microbial antigens. The age incidence of these conditions, the marked female excess, increase with economic and technological advance, precipitation by infection, and the paucity of histological changes are all consistent with the hypothesis. It can be tested directly using human sera to search for cross reaction with brain proteins in model systems such as Drosophila melanogaster . The conditions might be amenable to treatment using pooled immunoglobulin. Identification and elimination from the microbial flora of the bacteria that express the cross reacting antigens should be possible.